Morphometric Performance of Yearling Dorper × Local Sheep Crossbred Females Under Smallholder Farming Systems in Indonesia - Andri Andri; Graciano Lucky Scovier; Ali Mahmud; Aprilianna Putri Zahara Nafsina Luvita Sari; Yuli Arif Tribudi (Tarjih Tropical Livestock Journal, 2026)
Morphometric measurements of crossbred sheep at one year of age play a crucial role in animal husbandry, particularly in evaluating performance, genetic selection, and enhancing livestock quality. Yearling age is a phase of active growth in sheep. This study aimed to describe the morphometric characteristics of yearling female crossbred sheep, a product of crossing Dorper rams with Thin-Tailed (DET) ewes. The research was conducted at Mitrarama88 Farm in Pandesari Village, Pujon Sub-district, Malang Regency. A total of 42 yearling crossbred female sheep were included in this study, selected through purposive sampling based on animal availability, confirmed health status, and reliable age identification. Animals were maintained under a smallholder management system and fed a combination of field grass and concentrate. The data obtained were analyzed using descriptive statistics, including mean, standard deviation, and coefficient of variation. The results showed that the mean ± standard deviation of body weight, body length, body height, chest girth, hip width, head length, and head width of the yearling crossbred female sheep were 28.89±4.10 kg, 60.67±5.37 cm, 53.93±4.87 cm, 69.34±5.94 cm, 17.82±3.17 cm, 14.70±1.44 cm, and 14.22±1.88 cm, respectively. The observed morphometric improvements are likely attributable to heterosis effects, although parental performance data were not available for direct comparison. These findings suggest that Dorper × DET crossbreeding programs hold significant potential for improving the growth performance of local sheep breeds and could serve as a foundation for more targeted genetic improvement programs.